2019
DOI: 10.1038/s41419-018-1249-7
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a disrupts GR-TEAD4-PPARγ2 positive circuits and cytoskeletal rearrangement in a β-catenin-dependent manner during early adipogenesis

Abstract: Adipogenesis is a process which induces or represses many genes in a way to drive irreversible changes of cell phenotypes; lipid accumulation, round cell-shape, secreting many adipokines. As a master transcription factor (TF), PPARγ2 induces several target genes to orchestrate these adipogenic changes. Thus induction of Pparg2 gene is tightly regulated by many adipogenic and also anti-adipogenic factors. Four hours after the treatment of adipogenic hormones, more than fifteen TFs including glucocorticoid recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…2B-D). As GR regulates genes mainly by binding to their promoters (26), and GR regulates TEAD4 transcription during adipogenesis (18). We hypothesized that TEAD4 is also a direct target of GR during breast tumorigenesis.…”
Section: Tead4 Is a Direct Target Of Gr In Response To Gcsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B-D). As GR regulates genes mainly by binding to their promoters (26), and GR regulates TEAD4 transcription during adipogenesis (18). We hypothesized that TEAD4 is also a direct target of GR during breast tumorigenesis.…”
Section: Tead4 Is a Direct Target Of Gr In Response To Gcsmentioning
confidence: 99%
“…More importantly, TEAD4 nuclear localization positively autoregulates its own transcription and increases its protein level in the trophectoderm lineage, and the high TEAD4 concentration facilitates its nuclear localization as a positive feedback response (17). Recently, it has been reported that the glucocorticoid receptor (GR) binds to the promoter of TEAD4 to regulate TEAD4 transcription during adipogenesis (18). The activity of TEADs is also regulated by its cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…In the canonical Wnt pathway, Wnt ligand inactivates GSK3 via phosphorylation to inhibit the phosphorylation of β-Catenin, leading the latter to stabilize and translocate into the nucleus in order to transcribe downstream target genes (48). This pathway is well established to inhibit adipogenesis (49,50) and promote bone formation (51-53); while upregulation of non-canonical associated proteins induces Runx2 expression (54,55), the main osteoblastogenic transcriptional factor. Thus, Adipsin likely inhibits Wnt signaling in order to determine the differentiation fate of BMSCs.…”
Section: Adipsin Primes Bmscs Toward Adipogenesis Through Inhibition Of Wnt Signalingmentioning
confidence: 99%
“…For each treatment, 5 images were taken randomly within each chamber via a Bio-Rad ZOE Fluorescent Cell Imager using a 20X objective. F-actin structures in individual cells were observed and categorized into three types (Park et al, 2019). Quantification of each type of F-actin structure was analyzed using Image J software (Park et al, 2019).…”
Section: Immunofluorescence Of F-actin (The Actin Cytoskeleton)mentioning
confidence: 99%
“…F-actin structures in individual cells were observed and categorized into three types (Park et al, 2019). Quantification of each type of F-actin structure was analyzed using Image J software (Park et al, 2019). Briefly, stress fibers, where F-actin stress fibers were observed both in the nucleus and cytoplasm; transition state fibers, where F-actin stress fibers were observed only in the cytoplasm; cortical structure fibers, where F-actin fibers were observed near the cellular membrane as cortical structures.…”
Section: Immunofluorescence Of F-actin (The Actin Cytoskeleton)mentioning
confidence: 99%